Diarrhea in Nunukan Regency, North Kalimantan Province, Indonesia: Descriptive Analysis 2020-2023 - Devi Savitri Effendy; Nunung Sari (Journal of Epidemiology and Health Science, 2025)
Background: Diarrheal disease remains a major public health challenge in developing regions, including Indonesia, due to its strong association with inadequate water, sanitation, and hygiene conditions. Nunukan Regency, characterized by its geographical and infrastructural constraints, continues to experience a substantial burden of diarrhea cases, particularly among vulnerable populations. Objectives: This study aimed to describe and analyze the temporal distribution of diarrhea cases in Nunukan Regency from 2020 to 2023 in order to identify trends and highlight implications for public health interventions. Methods: A descriptive observational study design was employed using secondary surveillance data on reported diarrhea cases in Nunukan Regency for the period 2020–2023. Data were analyzed using descriptive statistics and presented in the form of a bar chart to illustrate annual trends in diarrhea incidence. Results: The findings indicate a fluctuating trend in diarrhea cases over the study period. A total of 1,536 cases were reported in 2020, followed by a substantial increase to 3,371 cases in 2021. In 2022, the number of cases declined to 2,903, and a more pronounced reduction was observed in 2023, with 1,257 reported cases. Despite the decreasing trend in the latter years, the overall incidence of diarrhea remained relatively high. Conclusion: Diarrhea continues to represent a significant public health concern in Nunukan Regency, as evidenced by persistently high case numbers and notable annual fluctuations. Sustained and integrated interventions focusing on improving access to safe water, sanitation, and hygiene practices are essential to achieve long-term reductions in diarrheal disease incidence in the region.